الادارة المحلية والتحول في العملية الادارية في الجزائر - الارضية البيومترية في بلدية سيدي عامر: -2024-2016 - أنموذجا - عمرة مهديد (جامعة المسيلة, 2025)
Close monitoring of the evolution of local administrative systems has necessitated an openness to various phases of transformation in the administrative process. These systems have now come to reflect changes in every aspect of their structure. This issue formed the core of our study, which measured the impact of technological variables on each function of the administrative process—most notably, the effect of the biometric system on these functions across various municipalities in Algeria. The municipality of Sidi Ameur, during the period from 2016 to 2024, was selected as the sample for this study. The topic was addressed from three perspectives: the theoretical aspect concerning local administration and the administrative process; the second aspect analyzed the same phenomenon in Algeria, highlighting the features of transformation within the administrative process following the introduction of technological elements; and finally, the third aspect focused on analyzing the practical transformation using econometric models. It was observed that since 2016, which marked the beginning‫ of‫ the‫ biometric‫ system’s‫ integration‫ into‫ Algerian‫ municipalities, the explanatory variable during the 2016 –2024 period reflected Algeria’s‫effective‫integration‫into‫what‫is‫known‫as‫the‫e-Algeria project
Keywords: s: Local administration; administrative process; transformation; biometric system; e-Algeria